Visual perception and decision making in dynamic environments: An experimental study in volleyball - Velentzas, K.; Schaper, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
A spiked volleyball with a velocity of 16.9 ± 2.4 m/sec requires approximately 412ms to hurtle into the defense zone (Melrose, Spaniol, Bohling, & Bonnette, 2007). Taking into account the temporal structure and technical/tactical demand of floor defense, perceptual skills are crucial and affect athletes` performance (Neumaier, 1983; Vickers, 2007). The present study aims to provide evidences about the relationship between perceptual strategies and decision making in volleyball and to scrutinize differences in gaze control between athletes of different levels. Method: For this purpose, female volleyball players participate in our study [novices-NV (N = 15, intermediated-IV (N = 13), German U19 national team (N = 13)]. 48 spike actions recorded from the defender perspective (position 5) were presented in a random order. Reaction time is measured by keyboard entries (Presentation®) and gaze behavior was evaluated by a SMI® eye-tracker. Participants were asked to "read" and enter spikes` direction (five possible choices) on the keyboard as fast as possible. Reaction-time was calculated in relation to the hitting moment. Results: The analysis of the decisions` accuracy shows no significant differences between groups (X²(df = 2, n = 41) = 4.21). However, reaction time decreases significantly on increasing expertise [F(2, 41) = 15.88, p < .001, Tukey-HSD Post-Hoc (MNV = 478ms; MIN = 206ms; MU19 = -30ms)]. Eye tracking data reveal significant shorter fixations for higher expertise F(2, 41)= 4.428, p = .018, [(MNV = 237ms : MIN = 203ms); (MNV = 237ms : MU19 = 184ms)] but no differences regarding the number of the fixations. Discussion: The results of the present study match previous studies partly only. Differences in gaze strategies can`t be ascertained. However we found differences regarding the fixations` duration and the reaction time. The results indicate that experts are able collect and actualize information more efficiently by using almost the same gaze strategies as the novices.